Ten‐year trends in catheter ablation for ventricular tachycardia vs other interventional procedures in Australia. (13th September 2019) - Anderson, Robert D.; Lee, Geoffrey; Prabhu, Mukund; Patrick, Cameron J.; Trivic, Ivana; Campbell, Timothy; Chow, Clara K.; Kalman, Jonathan M.; Kumar, Saurabh
Abstract: Aims: Major technological and procedural advancements have reinvigorated catheter ablation as adjunctive therapy for drug‐refractory ventricular tachycardia (VT). We examined temporal trends in VT ablations as compared to other interventional cardiovascular procedures namely, percutaneous coronary intervention (PCI) and atrial fibrillation (AF) ablation in Australia. Methods and Results: A retrospective review of procedural numbers for VT ablations, AF ablations, and PCI was performed from 2008/09‐2016/17 the Australian Institute of Health, Welfare and Aging (AIHW), and Medicare Australia (MA) databases. Linear regression models were fitted to compare the trends in population‐adjusted procedural numbers over the 10‐year period. Data from the AIHW and MA sources respectively showed that (a) PCI had a 1.3% (AIHW data P  = .15) and 1.8% (MA data P  < .001) population‐adjusted increment per year, (b) AF ablations had a 12.7% ( P  < .001) and 11.7% ( P  < .001) per year population‐adjusted increment, and (c) VT ablations showed an 18% ( P  < .001) and 12.7% ( P  < .001) per year population‐adjusted increment. Growth of PCI was increasing at a lower rate than AF ablations ( P  < .001 for both AIHW and MA sources). Growth of VT ablation was significantly higher than AF ablations and PCI (AIHW: 18% vs 12.7% [ P  = .004] and 1.3% per year [ P  < .001]). Conclusion: Catheter‐based VT ablation has increased significantly in Australia over the last decade, consistent with worldwide trends, and now surpassing all ablation procedures, including AF ablation and PCI for CAD. This data highlight the provision of additional resources to match the increasing demand for VT ablation procedures in Australia.